ANALISIS BIAYA PRODUKSI DAN PENDAPATAN PADA USAHATANI PADI (Studi Petani Padi di Desa Polenga Kecamatan Watubangga) - Fadillah, Fadillah; Sabarudin, Sabarudin; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
“Analysis of Production Costs and Income in Rice Farming (Case Study of Rice Farmers in Polenga Village, Watubangga Subdistrict)” This study aims to evaluate the structure of production costs and the level of income earned by rice farmers in Polenga Village, Watubangga Subdistrict. The analysis shows that the total cost incurred by farmers for cultivation up to harvest reaches IDR 12,640,000. Meanwhile, the revenue obtained from the harvest is around IDR 28,470,000. Thus, the net profit gained by farmers per planting season is IDR 15,830,000. This amount represents the net income calculated from the difference between total revenue and production expenses. The volume of rice harvested per season is approximately 1.5 tons. Based on these findings, it can be concluded that rice farming activities in this area are profitable and feasible for further development. The system applied in managing production costs and maximizing income demonstrates high efficiency and profitability, making it a viable agricultural practice in Polenga Village, Watubangga Subdistrict.